2022
DOI: 10.1111/jphd.12493
|View full text |Cite
|
Sign up to set email alerts
|

Integrating oral health into community health worker and peer provider certifications in Michigan: A community action report

Abstract: Introduction: A multi-disciplinary, community-university-government collaboration resulted in the development of Oral Health for Community Workers, a brief, oral health online e-learning module. The e-learning module was designed to improve oral health literacy among frontline health workers who are members of underserved communities, and to address oral health disparities in safety net medical and behavioral health settings. Methods: Community-based participatory methods were used to design and evaluate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The trainings demonstrated improvement in dementia knowledge, increased awareness of dementia resources, and showed the value of the creation of a network of CHWs who can share experiences and best practices. Our training approach confirmed that CHWs can serve as effective trainers for their peers, and that trainings can be successfully delivered virtually (Lapidos et al, 2022; Willock et al, 2015).…”
Section: Discussionsupporting
confidence: 63%
“…The trainings demonstrated improvement in dementia knowledge, increased awareness of dementia resources, and showed the value of the creation of a network of CHWs who can share experiences and best practices. Our training approach confirmed that CHWs can serve as effective trainers for their peers, and that trainings can be successfully delivered virtually (Lapidos et al, 2022; Willock et al, 2015).…”
Section: Discussionsupporting
confidence: 63%